DESA BONJERUK SEBAGAI DESA WISATA BERBASIS ALAM DAN BUDAYA DI LOMBOK TENGAH - Murianto Murianto (Sekolah Tinggi Pariwisata Mataram, 2019)
Tourism villages was increased last few years. Many Tourism Villages have grew up with a variety of different characteristics. One of them is Bonjeruk Tourism Village with Natural and Cultural Attraction. Data collection methods used by observation, in-depth interviews with Purposive Sampling by conducting in-depth interviews directly with various tourism figures in Bonjeruk Village. There are several potential attractions of Bonjeruk Village, such as Kokoh Dalam (Big River) Bonjeruk, Paddy Fields (Rice Terrace), Bamboo Gardens (Traditional Bamboo Market), Traditional Market Bonjeruk, Raden Mas Ancient Mosque, Ancient Houses, and various types of traditional arts and Music Traditional that can used as a place of study and tourist attraction. The development of Bojeruk Tourism village has to develop through Planning. Organizing, Actuating. Controlling for sustainable development of the Bonjeruk Tourism Village program